Incidentally diagnosed anomalous left coronary artery from the pulmonary artery in a 76-year-old man undergoing preoperative evaluation: a case report and literature review - Guoao Zhu; Sirui Zeng; Zihua Bao (Frontiers in Cardiovascular Medicine, 2026)
Anomalous left coronary artery from the pulmonary artery (ALCAPA), also known as Bland-White-Garland syndrome, is a rare congenital coronary artery anomaly with an incidence of approximately 1 in 300,000 live births, accounting for 0.25%–0.5% of all congenital heart diseases. Without surgical correction, approximately 90% of affected infants die within the first year of life due to myocardial ischemia and heart failure. However, a small subset of patients with well-developed collateral circulation may survive into adulthood without marked symptoms. We report an incidentally diagnosed case of ALCAPA in a 76-year-old man who was admitted for benign prostatic hyperplasia and urinary retention and underwent cardiovascular evaluation before non-cardiac surgery. Electrocardiography showed sinus bradycardia and complete right bundle branch block, and ambulatory celectrocardiography documented frequent supraventricular premature beats and short supraventricular tachycardia runs without significant ST-T abnormalities. Echocardiography showed a dilated right coronary artery, a suspected coronary fistula, mild chamber enlargement, preserved left ventricular systolic function, and no typical resting segmental wall-motion abnormality. Coronary CT angiography (CTA), performed after cardiology consultation, demonstrated the left main coronary artery arising from the pulmonary trunk, a markedly dilated and tortuous right coronary artery, extensive collateral circulation among the right coronary artery, left coronary system, and bronchial arteries, and a high coronary artery calcium score of 941.74 Agatston units. Cardiac enzymes were not elevated, but formal stress testing and cardiac magnetic resonance imaging were not performed during the index admission. The management decision was therefore framed as individualized conservative follow-up rather than evidence that conservative treatment is generally safe in adult ALCAPA. This case illustrates the diagnostic value of CTA for defining coronary anatomy in late adult ALCAPA, the need for functional ischemia and scar assessment when feasible, and the therapeutic tension between guideline-based surgical recommendations and individualized decision-making in elderly patients with preserved resting ventricular function.